What is European criminology actually about? Evolution from 2021 to 20231 - Tamarit Sumalla, Josep Maria (European journal of criminology, 2025)
This study examines the evolution of European criminology from 2021 to 2023. It aimed to determine if there have been any changes in the topics that researchers are interested in and how these topics have evolved. These interests might be affected by societal changes, which could influence their ability to address societal problems. A topic modelling methodology was used to analyse the abstracts presented at the annual ESC conferences from 2001 to 2023. We identified 50 topics, clustered in six main thematic areas and observed their evolution over this time period. The analysis provides a description of the most and least prevalent topics, as well as those that are increasing and decreasing in prominence. The results show some transformation in researchers? interests, shifting from a focus on criminal behaviour to a more victim-centred view and the emergence of new topics related to the evolution of social sensitivities.